2021
DOI: 10.35542/osf.io/ztwbh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WhatsApp Audio and Video Chat-Based in Stimulating Students’ Self-Confidence and Motivation to Speak English

Abstract: This era of 4.0 industrial revolutions, lecturers, especially English lecturers have to be aware with the technology particularly mobile technology that can enhance their students’ English skills in utilizing social media such as WhatsApp to improve students’ English speaking ability in order that they can show high self-confidence and motivation to learn this international language. This research aimed at describing students’ day to day English speaking skills via WhatsApp group set as a platform for audio an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…By developing materials based on a need analysis, it is expected that it will be possible to actively engage the students to communicatively perform oral communication in English in their day to day interactions both on campus and in society more generally. This frequent practice in authentic contexts has the potential to promote students' independent learning, motivation, and enhance their speaking skills (Maulina, Noni, Basri, 2019). The findings of this analysis, the proposed speaking module called WhatsApp-Based speaking module (WABSIM) is developed and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…By developing materials based on a need analysis, it is expected that it will be possible to actively engage the students to communicatively perform oral communication in English in their day to day interactions both on campus and in society more generally. This frequent practice in authentic contexts has the potential to promote students' independent learning, motivation, and enhance their speaking skills (Maulina, Noni, Basri, 2019). The findings of this analysis, the proposed speaking module called WhatsApp-Based speaking module (WABSIM) is developed and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in socializing issues, many platforms can be used to instantly gain information from society, known as social media. Social media platforms enable people to stay flexible to communicate, connect, and interact in this digital era (Maulina et al, 2019;Maulina et al, 2020;Maulina et al, 2021;Saputra et al, 2021). Instagram originally is one of the social media that allows users to share, upload, and search amount of photos and short videos.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies investigating students' and teachers' perceptions of the implementation of mobile technology in English language learning revealed that both groups have favourable perceptions and attitudes towards the use of MALL in teaching and learning English [29], [41], [42], [43], [44], [45]. Several studies concurred that the incorporation of MALL promotes constructive English language learning experiences in several areas of language skills relative to the conventional teaching and learning practices, such as vocabulary learning [46], reading skills [30], [47], writing skills [28], [43], speaking skills [48], [49], and listening skills [50], [51]. In addition, several studies also reported the positive effects of mobile technology on students' autonomy [24], [52] and motivation in learning English [53], [54].…”
Section: 1mentioning
confidence: 99%